ChemInform Abstract: [C16MPy]AlCl3Br: An Efficient Novel Ionic Liquid for Synthesis of Novel 1, 2, 4‐Triazolidine‐3‐thiones in Water. Issue 48 (2nd December 2014) - Patil, Jayavant D.; Pore, Dattaprasad M.
Abstract The applied catalyst is prepared in two steps from N‐methyl pyrrolidine.